Dasar Al-Qur’an Dan Hadits Tentang Kepemimpinan - Irka Muliyanty; Hamdanah Hamdanah; Noor Fahmi (Journal on Education, 2024)
Leadership in Islam is not just a position of power, but rather a moral responsibility that binds leaders to the principles of ethics and justice contained in the Koran and Hadith. This article explains the concepts and characteristics of leadership from an Islamic perspective, as well as their relevance in the contemporary context. Using a literature review approach, this article explores the basis of the Qur'an and Hadith regarding leadership, identifying the characteristics of effective leaders, such as honesty, trustworthiness, communication skills, and intelligence. Through a deep understanding of Islamic teachings on leadership, it is hoped that leaders can build a just, just and prosperous society, as well as strengthen inter-religious and inter-cultural dialogue in a multicultural society. With awareness of moral and social responsibility in leadership, it is hoped that a harmonious, prosperous and just community will be created.